2021
DOI: 10.1029/2020gb006706
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Manganese Oxide Formation Hinders Cobalt Scavenging in the Ross Sea

Abstract: Phytoplankton productivity in the Southern Ocean is an important sink for CO 2 (Arrigo, Robinson, et al., 1999) and accounts for 5%-10% of total global oceanic primary production (Arrigo et al., 2008;Moore & Abbott, 2000). While the Southern Ocean is generally considered to be iron (Fe) and light-limited (Alder-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 89 publications
2
16
0
Order By: Relevance
“…In contrast, Mn oxidation is absent in the surface Sargasso Sea throughout the day and night, whereas it is present in the dark subsurface (Sunda & Huntsman, 1988). Oldham et al (2021) did not detect pMn(IV) formation in either sun-lit surface or dark subsurface waters in the Ross Sea. The conditions that govern the diel Mn redox cycle are not clear, but have important implications for availability of Mn and other pMn-associated micronutrients.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In contrast, Mn oxidation is absent in the surface Sargasso Sea throughout the day and night, whereas it is present in the dark subsurface (Sunda & Huntsman, 1988). Oldham et al (2021) did not detect pMn(IV) formation in either sun-lit surface or dark subsurface waters in the Ross Sea. The conditions that govern the diel Mn redox cycle are not clear, but have important implications for availability of Mn and other pMn-associated micronutrients.…”
Section: Discussionmentioning
confidence: 62%
“…Factors such as temperature and microbial communities may lead to higher light‐dependent Mn reduction rates at the shelf stations compared to basin stations. Alternatively, given the high concentrations of humic substances in the Chukchi Sea (Hioki et al., 2014; Nakayama et al., 2011), it is possible that Mn oxidation at night was inhibited at shelf stations (6, 61, and 66) due to strong dissolved Mn(III)‐ligand complexes (Oldham et al., 2021). However, the inhibition of Mn oxidation cannot be a universal phenomenon in the Chukchi Sea, since slope Station 60 has a high AOS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations imply that northwards export of SW might not constitute a major off-shelf flux of DFe in the western Ross Sea. Oldham et al (2021) have recently reported much higher concentrations of DMn in water column samples from the western Ross Sea compared to the values measured in our PIPERS samples and from previous studies that collected samples during austral spring and summer (Gerringa et al, 2020;Sedwick et al, 2000). For stations sampled in February-March 2018, including stations in Terra Nova Bay, Oldham et al (2021) report an average concentration of 10 ± 14 nM for total dissolved manganese, which was comprised of varying proportions of Mn(II) and organically complexed Mn(III); they suggest that these relatively high DMn concentrations may reflect the precipitation of dissolved Mn(III)-humic complexes upon acidification of filtered samples in previous studies.…”
Section: Dissolved Trace Metalsmentioning
confidence: 99%